Il CPR dell’Ortica. Etnografia di un rimosso urbano in un quartiere in via di riqualificazione - Russo, Barbara (Antropologia Pubblica, 2024)
This present study aims to investigate the evolution of the relationship between the Administrative Detention Center of Milan, now referred to as CPR and located in Via Corelli, and the neighborhood in which it is located, the Ortica area in Lambrate, in the eastern suburbs of the city. Through an examination of this relationship and its temporal evolution, it is possible to develop an analysis of the interplay between the Centers designated for administrative detention and the social and economic dynamics of the surrounding territories. This investigation reveals how changes in urban dynamics correspond to shifts in the local role of the Center and its perception by the longstanding residents of the neighborhood. To conduct this analysis, we will integrate two levels of research. On one hand, we will review the history of migrant housing in the Lambrate neighborhood from the 1990s to the present, tracing a trajectory of progressive confinement of migrant populations from informal living spaces to an initial reception center and subsequently to the current CPR in Via Corelli. On the other hand, we will contextualize this phenomenon within the urban planning and socio-economic history of a former Fordist periphery and a district undergoing requalification. This involves associating the identified stages in the management of migrant presence in the neighborhood with significant moments in the transformation of spatial valorization processes within the urban territory.